Improving the role of global conservation treaties in addressing contemporary threats to lions - Hodgetts, T; Lewis, M; Bauer, H; Burnham, D; Dickman, A; Macdonald, E; Macdonald, D; Trouwborst, A (Springer Verlag, 2018)
Despite their iconic status, lion (Panthera leo) populations continue to decline across the majority of their range. In the light of the recent decision (in October 2017) to add lions to the Appendices of the Convention on Migratory Species (CMS), this paper identifies the new and existing legal protections afforded to lions through five global treaties, and maps these protections against the most critical contemporary threats facing the species. It thus offers a new analysis of the CMS listing, and draws on existing legal reviews, to highlight the ways in which global treaties offer differing forms of protection for lions. It then combines multiple concordant assessments of lion populations, to highlight nine categories of threat: human-lion conflict, bushmeat poaching, human encroachment, trophy hunting, trade in lion bones, unpredictable environmental events, socio-economic factors, policy failures, and governance/institutional weakness. The paper assesses how the various treaties each address these different categories of threat. The analysis identifies two pathways for improving legal protection: expanding the application of global treaties in respect of lions and their habitats (the paper considers the CMS listing in these terms), and improving the implementation of treaty commitments through local and national-scale actions. Furthermore, it identifies local implementation challenges that include the local knowledge of rules, compliance with rules and enforcement capacity, alongside the variety in local contexts and situations, and suggests where global treaties might provide support in meeting these challenges. We suggest that this analysis has wider implications for how treaty protection can and is utilised to protect various species of large-bodied, wide-ranging animals.